Analisis Indikator Entomologi dan Karakteristik Kontainer Larva Aedes aegypti di Kelurahan Bonto Sunggu Kabupaten Bantaeng - Nurul Auliyah Yusuf; Abd. Gafur; Nasruddin Syam (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
The Dengue Virus causes Dengue Hemorrhagic Fever (DHF) through the bite of the Aedes aegypti mosquito. Based on data from the Bantaeng Regency Health Office, Bonto Sunggu Village reported the highest number of DHF cases in Bantaeng Regency in 2023, with 10 cases. This study aims to determine the density of Aedes aegypti larvae using entomological indicators and to determine the factors that influence larval density. This type of research employs a cross-sectional study design. The population in this study was all containers in Bonto Sunggu Village, Bantaeng Regency. The sampling technique employed was simple random sampling. The number of samples was 100 containers located inside and outside the houses. The data analysis method used a bivariate test with a chi-square test. From the research results, it was found that the density level and risk of dengue fever transmission in Bonto Sunggu Village were still high, there was a significant relationship between the type of container with p value = 0.000, the location of the container with p value = 0.000 and the presence of a cover with p value = 0.000 on the density of Aedes aegypti larvae and there was no significant relationship between the container material with p value = 0.749, the color of the container with p value = 0.382 on the density of Aedes aegypti larvae.